ASYNCRFJ: uma abordagem assíncrona à programação orientada a objeto reativa - Cardoso, Diogo João (2018)
The presence of reactive programming has been more common in current systems, one of the highlights of its use is the management of input data streams. In the reactive programming paradigm, a new value for the input stream can be seen as an event, which may cause changes in the program, so it needs to be properly propagated. In this work is discussed the creation of a reactive programming language implementing the object-oriented paradigm (OO), allowing manipulation of classes and objects, where reactive expressions and data are modeled as an extension for Featherweight Java (FJ). This language is formally defined through the operation semantics, creating the opportunity to be implemented in any language that provides closures. An interpreter for the formalized language is also presented, that includes lexical, syntactic and semantic analysis, with its focus on the type system to embed reactive programming concepts in a classical language, demonstrating the interaction between the two reviewed paradigms.